للأداء المتميز في الجامعات العراقية (Malcolm Baldrige, 2011-2012) قياس درجة توفر القيم الجوهرية لجائزة : دراسة استطلاعية لآراء عينة من القيادات الإدارية في جامعة تكريت - أحمد علي حسين (PROSPECTIVE RESEARCHES, 2023)
One of the most important goals sought the research tries to achieve is to measure the availability degree of the core values of the Award (Malcolm Baldrige, 2011-2012) for excellent educational performance in Iraqi universities. The research is valuable because it is concerned with a major organization which must be promoted in performance for best. The sample of the research includes (67) members of administrative leadership at Tikrit University. (T-Test), arithmetic mean, standard deviations and relative weights are used to test the first hypothesis of the research for measuring the degree. The research comes up with a set of conclusions; the most important one is the availability of most core values degree of the Award (Malcolm Baldrige, 2011-2012) for excellent educational performance in Tikrit University A matter which reflects the effective efforts of the university. The researcher suggests a set of recommendations; among them is the need for recognizing that the university must pay a great equal care of all the core values of the Award (Malcolm Baldrige, 2011-2012) for excellent educational performance.